Coping with recession in the ski-industry: A suppliers’ and consumers’ perspective - Taks, Marijke; Ragoen, Jona (Université d'Ottawa | University of Ottawa, 2016)
The current study explores the impact of the recession on the ski industry based on interviews with suppliers in two ski resorts (n=10) as well as ski travel agencies (n=8). Subsequently, Flemish ski tourists (n=252) were surveyed about changes in their behavior towards ski vacations from 2008 to 2011, taking into account their socio-cultural background as well their level of ski/snowboard participation. Both studies reveal a decline in ski tourism during the years under investigation. The impact of the recession varies according to the type of sports provider. The impact of the recession on ski vacations is more prevalent for some groups in society (e.g., households with no children, more financial constraints, lower professional status, younger people), regardless of if one is a highly motivated and/or experienced skier. This paper contributes to socio-economic theory related to the ski tourism industry and assists suppliers to identify strategies to overcome hurdles during a recession.
Keywords: Demand; Industry; Recession; Skiing; Snowboarding; Supply; Volatility